"Wait With Falling in Love": Discursive Evaluation of Amicable Messages Conveyed by Opponents. (March 2021) - Kampf, Zohar; Chudy, Dana; Danziger, Roni; Schreiber, Mia
Amicable messages delivered in a conflict may have a positive effect on recipients' willingness to reconcile. Although studies have examined their effect, we still lack understanding on what grounds amicable messages are accepted or rejected. This study identifies the interpretative repertoires Israeli news commenters apply to make sense of amicable messages delivered unexpectedly by foreign opponent leaders, and demonstrates how they are employed for drawing epistemic boundaries between members of an interpretative community. Analysis of 2, 037 comments to reported messages toward Israel in the context of the Israeli–Palestinian conflict reveals 11 evaluative categories employed by Israeli commenters within two interpretative repertoires: suspicion and opportunity . Most commenters rejected the messages on grounds of the source's lack of credibility. A minority of commenters accepted the messages, focusing on wishful outcomes and in-group policies. The conclusion discusses the importance of studying interpretative repertoires and their applicability to other communities involved in conflicts.